Pengaruh Leverage Terhadap Kinerja Perusahan dengan Corporate Governance Sebagai Variabel Moderating - Ade Irma Fatika Retna (CV. Syntax Corporation Indonesia, 2021)
The purpose of research is to prove the influence of leverage on the company's performance and empirically that Corporate Governance is able to strengthen the influence of leverage on company performance. This research is quantitative research. The research sample was a manufacturing company listed on the Indonesia Stock Exchange from 2014-2018. The research data is the annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange published in 2014-2018. The company's annual financial statements can be accessed through the website www.dx.co.d. Data analysis techniques use regression analysis and classical assumption tests consisting of normality tests, multicollinearity tests, heteroskedasticity tests, and autocorrelation tests. The results of the analysis showed that Leverage had a positive effect on the company's performance in the basic and chemical industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2014 - 2018 with a thitung value of = 3.446 with a significant value of 0.001 < 0.05. (2) Corporate governance as a moderation variable does not moderate the influence of leverage on the company's performance in the basic industrial and chemical sector manufacturing companies on the Indonesia Stock Exchange (IDX) for the period 2014-2018 with a coefficient value of regression coefficient of moderation variable (Leverage*Corporate Governance) of -0.345 negative value with a significance value of 0.731 > α (0.05